YAYASAN USM TO HELP USM ACHIEVE ITS MISSION AND GOALS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 24 October 2016 Yayasan USM (USM Foundation) was established with the noble intention of accruing funds to assist the university in the implementation of various projects to achieve its mission and goals.